Shopping and consumer culture in Palmerston North c. 1945-85 : presented in partial fulfilment of the requirements for a Master of Arts in History at Massey University - Durkin, Kate (Massey University, 2026)
The aim of this thesis is to investigate the different meanings of shopping and consumerism between 1945 and 1985 in Palmerston North, New Zealand. Shopping and Consumer culture in Palmerston North are examined within the wider context of both specific developments in Palmerston North and contemporary trends in New Zealand. Shopping and consumer culture are investigated in three categories. Chapter Two examines changing trends in consumer culture in central city department stores. Chapter Three investigates shopping and consumer culture in suburban contexts, including the Manawatu Co-Op network and the emergence of seniors as a consumer group in their own right. Chapter Four focuses on the impact of Massey University on shopping and consumer culture, in particular the emergence of students as a market for local stores. The relationship between shopping, consumer culture and gender roles will also be discussed during the thesis, as this was an important dynamic in the period under review.
Figures in footnotes 145, 182, 397, 468 & 521 are reproduced with permission.
Keywords: 430320 New Zealand history